Pengaruh perputaran kas, perputaran persediaan terhadap return on assets pada PT. Unilever Indonesia Tbk periode 2015-2024 - Karundeng, Tesalonika Syalomita; Lambey, Robert; Kalalo, Meily Y.B. (Yayasan Widyantara Nawasena Raharja, 2025)
This study investigates the effect of cash turnover and inventory turnover as key indicators of working capital management on Return on Assets (ROA) at PT Unilever Indonesia Tbk during the 2015–2024 period. Employing a quantitative explanatory research design, this study uses quarterly secondary data obtained from the company’s published financial statements, comprising 40 observations. The data are analyzed using multiple linear regression after meeting classical assumption requirements. The results reveal that cash turnover has a positive and statistically significant effect on ROA, indicating that efficient cash utilization enhances corporate profitability. Inventory turnover also exerts a positive and significant influence on ROA, reflecting the importance of inventory efficiency in optimizing asset performance. Furthermore, both variables simultaneously have a significant impact on ROA, demonstrating the critical role of effective working capital management in corporate financial performance. These findings are consistent with signaling theory, where efficient asset management conveys positive signals regarding firm value and operational efficiency to investors. This study provides empirical evidence that strengthening cash and inventory turnover is essential for improving profitability and financial efficiency in large manufacturing firms within the consumer goods sector.